Multidrug resistance regulators (MDRs) as scaffolds for the design of artificial metalloenzymes. Issue 14 (21st March 2017) - Bersellini, Manuela; Roelfes, Gerard
Abstract : Artificial metalloenzymes were created from multidrug resistance regulator proteins by in vivo incorporation of an unnatural metal binding amino acid. Abstract : The choice of protein scaffolds is an important element in the design of artificial metalloenzymes. Herein, we introduce Multidrug Resistance Regulators (MDRs) from the TetR family as a viable class of protein scaffolds for artificial metalloenzyme design. In vivo incorporation of the metal binding amino acid (2, 2-bipyridin-5yl)alanine (BpyA) by stop codon suppression methods was used to create artificial metalloenzymes from three members of the TetR family of MDRs: QacR, CgmR and RamR. Excellent results were achieved with QacR Y123BpyA in the Cu 2+ catalyzed enantioselective vinylogous Friedel–Crafts alkylation reaction with ee's up to 94% of the opposite enantiomer that was achieved with other mutants and the previously reported LmrR-based artificial metalloenzymes.